2000
DOI: 10.1128/iai.68.3.1176-1182.2000
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Family of Proline-Specific Peptidases of Porphyromonas gingivalis : Purification and Characterization of Serine Dipeptidyl Peptidase, a Structural and Functional Homologue of Mammalian Prolyl Dipeptidyl Peptidase IV

Abstract: Porphyromonas gingivalis is an asaccharolytic and anaerobic bacterium that possesses a complex proteolytic system which is essential for its growth and evasion of host defense mechanisms. In this report, we show the purification and characterization of prolyl dipeptidyl peptidase IV (DPPIV) produced by this organism. The enzyme was purified to homogeneity, and its enzymatic activity and biochemical properties were investigated. P. gingivalis DPPIV, like its human counterpart, is able to cleave the N terminus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 41 publications
6
63
1
Order By: Relevance
“…1). In accord with a previous report [14], recombinant DPPIV most preferentially hydrolyzed Gly-Pro-MCA, while that of Lys-Ala-MCA was less potent.…”
Section: Peptidase Activities Of Dpps Belonging To Clusters 1-5 From supporting
confidence: 92%
“…1). In accord with a previous report [14], recombinant DPPIV most preferentially hydrolyzed Gly-Pro-MCA, while that of Lys-Ala-MCA was less potent.…”
Section: Peptidase Activities Of Dpps Belonging To Clusters 1-5 From supporting
confidence: 92%
“…Together with the present and previous observations of PgDPP4, including the kinetic parameters of enzymatic reactions, optimal pH, inhibitor profiles, and substrate preference for Pro and less for Ala (15,18,31), our results led us to conclude that the enzymatic properties of bacterial DPP4 substantially resemble those of the human entity (28,38). In fact, the present findings revealed release of the N-terminal dipeptide from the incretin peptides GLP-1 and GIP by bacterial DPP4.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, similar masses between recombinant and native DPP4 suggested that major posttranslational modifications did not occur in bacterial entities. Indistinguishable activities between native and recombinant PgDPP4s were reported previously (18,32). In addition, molecular masses of recombinant and native forms of DPP4 were estimated as approximately 9% smaller than those of the deduced sequences.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations